Analysis of Teaching Material Needs as a Basis for Learning Management in the Hindu-Buddhist Civilization History Course - Wahid Ibrahim Banul Ngindom; Nur Ahyani; Kabib Sholeh (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aims to analyze the needs for teaching materials in the Hindu–Buddhist Civilization History course in the History Education Study Program at Universitas PGRI Palembang. The research employed a descriptive qualitative approach using a needs analysis design. Participants consisted of 73 students who had completed the course and 3 lecturers responsible for teaching the subject. Data were collected through questionnaires, semi-structured interviews, and document analysis of curriculum and existing teaching materials. Descriptive statistical analysis and thematic qualitative analysis were applied. The findings reveal a strong need for systematically organized printed teaching materials integrated with digital learning resources. Students reported high demand for coherent content structure, visual presentation, and access to online historical resources. Lecturers emphasized the importance of blended print–digital materials to support effective learning management. This study provides practical implications for the development of integrated teaching materials that can be directly utilized to improve instructional planning and learning effectiveness in history education.